Handling Cash In And Cash Out On Dimas Mart Supermarket Kampar Regency - Delfian Zaman; Dina Dina (Fakultas Ekonomi dan Bisnis Islam, 2022)
In general, every company, both small and large, must have Cash In and Cash Out. Cash has a central position in maintaining smooth operations. Cash also has the nature that its ownership cannot be proven and is easily transferred, so it is easy to misappropriate or embezzle. Therefore, it is necessary to carry out strict cash supervision, and there must be proper reporting of its use. The company must be careful in carrying out activities related to Cash In and Cash Out, meaning that every cash recipient and cash disbursement transaction must be recorded so that unwanted deviations do not occur. Cash receipts and disbursements must be carried out effectively and efficiently, so there is no budget waste. Therefore, we need an adequate system to be able to monitor cash receipts and cash disbursements. This research aims to explain how to handle cash inflows and outflows and how to handle cash bookkeeping at the Dimas Mart supermarket. So that the supermarket can improve procedures for handling cash inflows, cashouts, and cash bookkeeping so that it can be a reference in conducting similar research at a place and time. Different.